2007
DOI: 10.1111/j.1467-9590.2007.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Universally‐Convergent Squared‐Operator Iteration Methods for Solitary Waves in General Nonlinear Wave Equations

Abstract: Summary:Three new iteration methods, namely the squared-operator method, the modified squaredoperator method, and the power-conserving squared-operator method, for solitary waves in general scalar and vector nonlinear wave equations are proposed. These methods are based on iterating new differential equations whose linearization operators are squares of those for the original equations, together with acceleration techniques. The first two methods keep the propagation constants fixed, while the third method kee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
164
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(165 citation statements)
references
References 30 publications
0
164
0
Order By: Relevance
“…(3.3) and (3.4). In Example 4.1 in Section 4, we demonstrated that this technique can be superior to an alternative, squared-operator, technique [8] when applied to finding lowest-order nonfundamental solutions. However, for finding higher-order solutions, the technique of Ref.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…(3.3) and (3.4). In Example 4.1 in Section 4, we demonstrated that this technique can be superior to an alternative, squared-operator, technique [8] when applied to finding lowest-order nonfundamental solutions. However, for finding higher-order solutions, the technique of Ref.…”
Section: Discussionmentioning
confidence: 94%
“…However, for finding higher-order solutions, the technique of Ref. [8] appears to be more practical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, a number of numerical methods have been developed. Examples include the Newton's method [1,2], the shooting method [3], the Petviashvili-type methods [4][5][6], the accelerated imaginary time evolution methods [7,8], the squared-operator iteration methods [9], etc. The Newton's method is a classical iteration method.…”
Section: Introductionmentioning
confidence: 99%
“…The stationary solution with real propagation constant b is looked for as q(ξ, η, ζ) = u(ξ, η)e ibζ , where complex function u(ξ, η) obeys equation To find the stationary self-trapping solutions, we used numerical simulations with the modified squaredoperator method [48]. While the existence and stability of the simplest single-beam solitons in the present setting is quite evident, as the first step of the analysis we produce double-beam self-trapped states.…”
Section: (A)mentioning
confidence: 99%